Analisis Faktor Perencanaan Pendidikan: Politik, Identitas Nasional, Ekonomi, Agama, dan IPTEK - Layalil Maghfiroh Zain; Samsul Susilawati (Al-Kindi, 2026)
Educational planning is a strategic process influenced by various interrelated internal and external factors. This study aims to analyze how political, national identity, economic, religious, and science and technology (S&T) factors have a positive impact as well as pose challenges to the development of education in Indonesia. This study uses a qualitative approach with a literature review method, namely by examining books, national and international journals, and relevant previous studies. The results of the study show that politics plays a dominant role in directing education policy, but overly dynamic policy changes often lead to inconsistencies. National identity has proven to be important in shaping the character and identity of students through the internalization of national values. Economic factors are a major determinant of the quality and equity of education, while religion provides a moral foundation for the formation of students' personalities. Meanwhile, advances in science and technology encourage learning innovation, but also present challenges in the form of the digital divide and infrastructure limitations. Overall, this study concludes that effective educational planning must consider all these factors in an integrated manner so that the education system can develop in a sustainable, relevant, and adaptive manner in response to changing times.